An inequality for eigenvalues of quasilinear problems with monotonic weights - Castro, M.J. (2010)
In this work we extend an inequality of Nehari to the eigenvalues of weighted quasilinear problems involving the p-Laplacian when the weight is a monotonic function. We apply it to different eigenvalue problems. © 2010 Elsevier Ltd. All rights reserved.